2014
DOI: 10.1002/app.41143
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of pressure sensitive adhesives from a fatty ester

Abstract: Novel pressure sensitive adhesives (PSAs) were developed from renewable methyl oleate (MO) and fully evaluated for their peel strength, tack force and shear resistance. MO was epoxidized and selectively hydrolyzed on the ester group to form epoxidized oleic acid (EOA) that is a bifunctional monomer containing both a carboxylic acid group and an epoxy group. EOA was step‐growth polymerized to form a hydroxyl‐containing polyester, which was then cured in the presence of a small amount of a polyfunctional epoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…By exploiting these functional groups, vegetable oils have been successfully used as renewable starting materials for the preparation of a large variety of monomers and polymers . Some fields of application include epoxy resins, polyurethane resins, and pressure‐sensitive adhesives …”
Section: Introductionmentioning
confidence: 99%
“…By exploiting these functional groups, vegetable oils have been successfully used as renewable starting materials for the preparation of a large variety of monomers and polymers . Some fields of application include epoxy resins, polyurethane resins, and pressure‐sensitive adhesives …”
Section: Introductionmentioning
confidence: 99%
“…EOA was step-growth polymerized to form a hydroxyl-containing polyester, which was then cured in the presence of a small amount of ESO to afford PSAs. The step-growth polymerization of EOA is shown in Figure 30 (116). ESO had multiple epoxy groups on each ESO molecule, and could consume the carboxylic acid groups of the impurities and crosslink the carboxylic acid groups at the chain end of PEOA.…”
Section: Eso As a Crosslinker For Psasmentioning
confidence: 99%
“…However, the process for the preparation of PSAs may not be environmentally friendly. During the preparation, an organic solvent such as toluene has to be used to dissolve natural rubber so that the natural rubber can be coated on films or paper for the production of tapes and labels (116).…”
Section: Pressure Sensitive Adhesivesmentioning
confidence: 99%
“…It has also been reported that PSAs can be developed from the curing of polyesters from the condensation of dimer acid (DA) and diols with epoxidized plant oils (10,11). PSAs can also be developed from the polymerization of an AB-monomer, epoxidized oleic acid (12,13). It has been demonstrated that a mixture of epoxidized fatty acids (EFAs) can be efficiently produced from the selective hydrolysis of epoxidized soybean oils (14).…”
Section: Introductionmentioning
confidence: 98%